The Guitar improvisations of Mwenda Jean Bosco - Rycroft, David K. (International Library of African Music, 1961)
Mwenda Jean Bosco’s improvised guitar songs—particularly his Masanga—are by this time widely known and appreciated. This has been due, initially, to the wide circulation of his records after he became one of Hugh Tracey’s “discoveries” and, as a direct result of this, to his popularity as a radio personality in Central and East Africa. This initial article has been confined to consideration of two of Bosco’s earliest recorded works, Masanga—both in its guitar-accompanied song version and as a guitar solo—and Bombalaka, a guitar song. Attention will be paid to the guitar music rather than to the vocal line. A later article will provide transcriptions of ten more of his works, all of them guitar songs, and attempt a comparative treatment of his style.
Keywords: Guitarists; Ethnomusicology; Zaire; African Music